Aktivitas Penghambatan Enzim α-Glukosidase oleh Ekstrak Etanol Umbi Ubi Jalar Ungu (Ipomoea batatas L.) - Elmaniar, Rahmi, Dr.Muhtadi, M.Si (2017)
Diabetes mellitus is a metabolism disorder that marked with a hyperglycemia. One of drugs that used for treat diabetes mellitus is by inhibit α-glucosidase enzyme. Purple sweet potato (Ipomoea batatas L.) is one of plants that have potential for medicine antidiabetics. This research aims to determine the extract of ethanol purple sweet potato (Ipomoea batatas L.) had an activity inhibition of the enzyme α-glucosidase, and kinetical mechanism inhibition α-glucosidase enzyme. The inhibition activity of the enzyme α-glucosidase measured by spectrophotometry method which read with ELISA reader at a wavelength 405 nm. The activity an enzyme measured based on the formation of compounds p-nitofenol yellow color. Enzyme inhibition kinetics done to determine the type of enzyme inhibition using the inhibitor and without inhibitor to obtained Lineweaver-Burk curve. Ethanol extract of purple sweet potato (Ipomoea batatas L.) could inhibited α-glucosidase enzyme. The percentage of inhibition was 51.18% at 25 ppm. Based on Lineweaver-Burk curve that y ≠ 0 and x ≠ 0 and the value of KAP > K and VAP < V, the type kinetics inhibition of ethanol extract of purple sweet potato (Ipomoea batatas L.) was mixed type.